(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2024)
Proteins are needed by all living cells for structural and functional purposes. However, some proteins such as liposome instability may result in medication leaks that could harm cells. The detection of liposomes is dependent on the complex interactions between proteins, which are necessary for both their structural integrity and functional characteristics. This emphasizes the critical role that proteins play in the precise identification and examination of liposomal structures. Ion-sensitive field-effect transistor (ISFET) biosensor has gained popularity in the clinical research field for biomolecule detection due to its high detection sensitivity, mass-production capability, and low manufacturing cost. Nanohub BioSensorLab software was used to analyze the performance of different structures of ISFET (planar, cylindrical nanowire, nanosphere and double-gate FET) by simulating the settling time and selectivity of the biosensors. As the structural dimension expands from 1D to 3D, the settling time increases by three folds at the lowest analyte concentration. The fastest settling times were achieved by planar ISFET and double-gate FET. For selectivity measurements, an enhanced selectivity was achieved by increasing the concentration of the target molecule and decreasing the concentration of the parasitic molecule. A higher selectivity is determined by the higher Signal-to-Noise Ratio (SNR) value. The SNR increased linearly corresponds to the increase in the concentration of the target molecule as well as the decrease in the parasitic molecule’s concentration. The parasitic molecule’s size increase of 1 nm causes a rise in SNR of 5.00×103.